Some hydrozoans (Cnidaria) from Central Chile and the Strait of Magellan - Galea, Horia R.; Schories, Dirk (Zootaxa, 2012)
This report supplements a series of earlier accounts on the hydrozoan fauna of Chile, and discusses 34 species of hydroidsand one hydromedusa. The available collection was gathered from three distinct biogeographical regions: the southernborder of the Peruvian Province around Punta de Choros, the southern Intermediate Zone around Corral, and the northernand southern parts of the Magellan Province, around Reloncaví Sound and in the Strait of Magellan, respectively. All thespecies are fully illustrated and, when necessary, data on the cnidome composition are provided. Six species, Haleciumannuliforme, Sertularella curvitheca, Sertularella mixta, Symplectoscyphus patagonicus, Halopteris plumosa, and Clytiareloncavia, are described as new. The gonothecae of Halecium fjordlandicum Galea, 2007, Symplectoscyphusmagellanicus (Marktanner-Turneretscher, 1890), and Campanularia hartlaubi (El Beshbeeshy, 2011) are described for thefirst time, while those of Kirchenpaueria curvata (Jäderholm, 1904) were rediscovered and are accurately redescribed.Morphological differences between C. hartlaubi and C. lennoxensis (Jäderholm, 1903), two species with similartrophosomes, are highlighted. Large, fertile specimens of Halecium pallens Jäderholm, 1904, as well as a female colonyof Hydractinia parvispina Hartlaub, 1905, allowed new redescriptions to be made. Due to insufficient taxonomicinformation on several species created more than a century ago, two Chilean records are doubtfully assigned toSertularella implexa (Allman, 1888) and Sertularella lagena Allman, 1876, respectively, the former represented by fertilespecimens, and thus allowing the first description of its gonothecae. The long history of the confused taxonomy of SouthAmerican "Symplectoscyphus subdichotomus (Kirchenpauer, 1884)" is now entirely settled. All the available records areconfidently assigned to the synonymy of Symplectoscyphus filiformis (Allman, 1888), whose sexual dimorphism ofgonothecae, first indicated by Totton (1930), is confirmed in light of the present material. Five species represent newrecords for the country: Staurocladia vallentini (Browne, 1902), Samuraia tabularasa Mangin, 1991, H. pallens,Sertularella blanconae El Beshbeeshy, 2011, and Symplectoscyphus paraglacialis El Beshbeeshy, 2011, the latter twobeing redescribed. Due to the scarcity of available material and the lack of gonophores of both sexes, six species ofEudendrium Ehrenberg, 1834 could be identified to genus only. Similarly, a species of Sertularella Gray, 1848 and twobelonging to Symplectoscyphus Marktanner-Turneretscher, 1890, are awaiting reliable identifications based on fertile specimens. A species of Clytia Lamouroux, 1812 could not be determined to species in the absence of life cycle studies.